If the area enclosed by the equation:
y = 3 6 + x 2 3 6 0
and the x axis can be represented as a π , find a
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice Solution.
Nice solution! It was a good intuition for me!`
Consider the integral ∫ a 2 + x 2 1 d x . Let x = a tan z so that d x = a sec 2 z . Putting these yields ∫ a 2 ( 1 + tan 2 z ) a sec 2 z d z = ∫ a sec 2 z sec 2 z d z = ∫ a 1 d z = a z + C = a arctan ( x / a ) + C . Notice that the function y = a 2 + x 2 1 is even. So we have ∫ − ∞ ∞ a 2 + x 2 1 d x = 2 ∫ 0 ∞ a 2 + x 2 1 d x = 2 a arctan ( x / a ) ∣ ∣ ∣ ∣ 0 ∞ = a π . Now plugging in a = 6 and multiplying by 3 6 0 gives our desired answer 6 3 6 0 π = 6 0 π .
Good solution.
I still have that "Table of Integrals" book with me since high school days, and this one is an oldie
∫ a 2 + x 2 1 d x = a 1 A r c T a n ( a x )
I didn't evaluate this integral as you have here. Thanks for the demonstration.
You're welcome. :D
Problem Loading...
Note Loading...
Set Loading...
From this question, what we are being asked is to find
∫ − ∞ ∞ 3 6 + x 2 3 6 0 d x
We can split this into
∫ − ∞ 0 3 6 + x 2 3 6 0 d x + ∫ 0 ∞ 3 6 + x 2 3 6 0 d x
From this, we can change both these integrals into
n → − ∞ lim ∫ n 0 3 6 + x 2 3 6 0 d x + m → ∞ lim ∫ 0 m 3 6 + x 2 3 6 0 d x
Now, let's work on the integrals.
∫ 3 6 + x 2 3 6 0 d x
Well, the denominator looks promising since it is in the form of a 2 + b 2 . In this case, a = 6 and b = x . We can now try to substitute x with a different value. For this, we will do
x = 6 tan θ
Now to make sure that we can substitute back, let's change the subject to θ .
6 x = tan θ
arctan ( 6 x ) = θ
We also need to find d x of 6 tan θ . Simplifying, we get
6 sec 2 θ d θ
Inputting these values back in the integral, we get
∫ 3 6 + ( 6 tan θ ) 2 3 6 0 ⋅ 6 sec 2 θ d θ
which is simplified as
∫ 3 6 + 3 6 tan 2 θ 3 6 0 ⋅ 6 sec 2 θ d θ
The denominator can be factorised to
∫ 3 6 ( 1 + tan 2 θ 3 6 0 ⋅ 6 sec 2 θ d θ
which simplifies the fraction as
∫ 1 + tan 2 θ 1 0 ⋅ 6 sec 2 θ d θ
Notice that 1 + tan 2 θ can be written as sec 2 θ . With this in mind, we simplify further to just
∫ 6 0 d θ
or
6 0 ∫ d θ
which is simply
6 0 θ + C
Now we substitute the value of x back in to get
6 0 ( arctan ( 6 x ) )
or
6 0 arctan ( 6 x )
Now we take this value back to the limits. Sustituting them, we get
n → − ∞ lim ( 6 0 arctan ( 6 x ) ) ∣ n 0 + m → ∞ lim ( 6 0 arctan ( 6 x ) ) ∣ 0 m
Now, if we simplify this, we get
n → − ∞ lim ( 6 0 arctan ( 6 0 ) − 6 0 arctan ( 6 n ) ) + m → ∞ lim ( 6 0 arctan ( 6 m ) − 6 0 arctan ( 6 0 ) )
Well, arctan ( 0 ) is just 0. For − ∞ , it's 2 − π and for ∞ , it's 2 π . Inputting these values, we get
( 6 0 ⋅ 0 − 6 0 ⋅ 2 − π ) + ( 6 0 ⋅ 2 π − 6 0 ⋅ 0 )
or just
3 0 π + 3 0 π = 6 0 π
Therefore, 6 0 is our answer. Upvotes would be appreciated since I spent over an hour on this solution.